Novel Strategies for Efficient Production and Delivery of Live Biotherapeutics and Biotechnological Uses of Lactococcus lactis: The Lactic Acid Bacterium Model - Tavares, Laísa M.; de Jesus, Luís C. L.; da Silva, Tales F.; Barroso, Fernanda A. L.; Batista, Viviane L.; Coelho-Rocha, Nina D.; Azevedo, Vasco; Drumond, Mariana M.; Mancha-Agresti, Pamela (Frontiers in Bioengineering and Biotechnology, 2020)
Lactic Acid Bacteria (LAB) are traditionally used in fermentation and food preservation processes and are recognized as safe for consumption. Recently, they have attracted attention due to their health-promoting properties; many species are already widely used as probiotics for treatment or prevention of various medical conditions, including inflammatory bowel diseases, infections, and autoimmune disorders. Some LAB, especially Lactococcus lactis, have been engineered as live vehicles for delivery of DNA vaccines and for production of therapeutic biomolecules. Here we summarize work on engineering of LAB, with emphasis on the model LAB, L. lactis. We review the various expression systems for the production of heterologous proteins in Lactococcus spp. and its use as a live delivery system of DNA vaccines and for expression of biotherapeutics using the eukaryotic cell machinery. We have included examples of molecules produced by these expression platforms and their application in clinical disorders. We also present the CRISPR-Cas approach as a novel methodology for the development and optimization of food-grade expression of useful substances, and detail methods to improve DNA delivery by LAB to the gastrointestinal tract. Finally, we discuss perspectives for the development of medical applications of recombinant LABs involving animal model studies and human clinical trials, and we touch on the main safety issues that need to be taken into account so that bioengineered versions of these generally recognized as safe organisms will be considered acceptable for medical use.